1998
DOI: 10.1002/(sici)1097-0274(199802)33:2<131::aid-ajim5>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory diseases among union carpenters: Cohort and case-control analyses

Abstract: Lung diseases, defined by ICD‐9 diagnoses on medical insurance claims, were studied through the combined use of administrative records, private health insurance, and workers' compensation claims for a cohort of 10,938 active union carpenters between 1989 and 1992. The cohort defined the study base for a nested case‐control study, in which cases (n = 220) were initially identified by an ICD‐9 code for asthma in private health insurance or workers' compensation files. A questionnaire was used to collect informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 35 publications
2
15
0
Order By: Relevance
“…The large excess observed for pleural cancers is largely explained by occupational exposures to asbestos, known to occur among carpenters. 32 An increase in rectal cancer and intestinal cancer contributed to the overall increase in the incidence of cancers of the digestive tract; whereas no increased risk of stomach cancer occurred. Some studies have noted an excess in morality due to stomach cancer with risk estimates ranging from 1.2 to 1.4, 6,7,11 as well as a case-control study that observed an elevated odds ratio (OR ϭ 1.7, 95% CI ϭ 1.0 -2.7) for stomach cancer among workers exposed to wood dust for at least 15 years.…”
Section: Discussionmentioning
confidence: 99%
“…The large excess observed for pleural cancers is largely explained by occupational exposures to asbestos, known to occur among carpenters. 32 An increase in rectal cancer and intestinal cancer contributed to the overall increase in the incidence of cancers of the digestive tract; whereas no increased risk of stomach cancer occurred. Some studies have noted an excess in morality due to stomach cancer with risk estimates ranging from 1.2 to 1.4, 6,7,11 as well as a case-control study that observed an elevated odds ratio (OR ϭ 1.7, 95% CI ϭ 1.0 -2.7) for stomach cancer among workers exposed to wood dust for at least 15 years.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it was not possible to estimate the selection bias. The age distribution was almost identical between the responded painters and carpenters with the possibility that the respondents could be older with more union experience than the non-respondents [Lipscomb and Dement, 1998;Kaukiainen et al, 2004]. The actual prevalence of respiratory symptoms could be lower than the results indicate, if the non-responders were to have less symptoms than the responders.…”
Section: Discussionmentioning
confidence: 84%
“…To our knowledge, the current questionnaire material is the most extensive among studies focusing on the respiratory health of construction painters [White and Baker, 1988;Wieslander et al, 1994aWieslander et al, ,b, 1997b. The adequate overall response rate of around 60% was the same as in a union carpenter study on respiratory diseases [Lipscomb and Dement, 1998] and probably influenced by (a) the fact that both occupational groups were male and (b) the level of detail requested in the questionnaire. The trade union was not able to allow non-respondent analysis for reasons of membership confidentiality.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations